The applicability of hidden resilience in the lives of adolescents involved in drug trafficking - Gomes Pessoa, Alex Sandro (2017)
This chapter aims to explore the manifestations and relevance of hidden resilience within the lives of Latin American adolescents involved in drug trafficking. Initially, we discuss the need to build a theoretical-methodological resilience framework based on the realities faced by the Latin American population. Next, we highlight implications of the concept of hidden resilience for adolescents and young people in situations of social exclusion. Following, by exploring a sample of adolescents’ and young adults’ narratives, we interpret the meaning that drug trafficking can acquire in the lives of adolescents, focusing on processes of hidden resilience that emerge in their narratives. Based on these interpretations - which are informed by the authors’ experience in youth resilience research coupled with the first author’s knowledge and field research on drug trafficking in the Latin American context - we propose restructuring the conversation on adolescents’ involvement in drug trafficking, in a way that more readily acknowledges social and historical contexts and builds upon manifestations of hidden resilience.